Fundamental Economic Variables, Expected Returns, and Bond Fund Performance - Elton, Edwin J.; Gruber, Martin J.; Blake, Christopher R. (Journal of Finance, 1995)
In this article, we develop relative pricing (APT) models that are successful in explaining expected returns in the bond market. We utilize indexes as well as unanticipated changes in economic variables as factors driving security returns. An innovation in this article is the measurement of the economic factors as changes in forecasts. The return indexes are the most important variables in explaining the time series of returns. However, the addition of the economic variables leads to a large improvement in the explanation of the cross-section of expected returns. We utilize our relative pricing models to examine the performance of bond funds.